2015
DOI: 10.1007/s00170-015-7539-7
|View full text |Cite
|
Sign up to set email alerts
|

Chip formation and its effects on cutting force, tool temperature, tool stress, and cutting edge wear in high- and ultra-high-speed milling

Abstract: In the present study, experimental tests and finite element simulation were conducted in order to investigate chip formation and its effects on cutting force, tool temperature, tool stress, and cutting edge wear in high-and ultra-highspeed (v=200∼2000 m/min) milling. It was found that the serration of chip became more and more obvious as the cutting speed increased. Most of the saw-tooth chip was separated at the cutting speed of 2000 m/min. During the formation process of the separated saw-tooth, the high tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 14 publications
(26 reference statements)
0
19
0
2
Order By: Relevance
“…Shatla [9] conducted two-dimensional (2D) orthogonal slot milling experiments in conjunction with analytical-based OXCUT and Oxley's method to obtain flow stress data for the metal cutting of AISI P20 (30 HRC) and AISI H13 (46 HRC), and analyzed the tool chipping and surface integrity of a machined workpiece employing an FEM that fitted the J-C constitutive equation of stress data. Cui [10] employed the J-C constitutive equation of AISI H13 (46-47 HRC) and conducted experimental tests and finite simulation to investigate chip formation in high-and ultra-high-speed milling. He found that the serration of chips became increasingly obvious as the cutting speed increased, the formation frequency of a sawtooth increased with decreasing growth, and most of the sawtooth separated at a cutting speed of 2000 m/min.…”
Section: Introductionmentioning
confidence: 99%
“…Shatla [9] conducted two-dimensional (2D) orthogonal slot milling experiments in conjunction with analytical-based OXCUT and Oxley's method to obtain flow stress data for the metal cutting of AISI P20 (30 HRC) and AISI H13 (46 HRC), and analyzed the tool chipping and surface integrity of a machined workpiece employing an FEM that fitted the J-C constitutive equation of stress data. Cui [10] employed the J-C constitutive equation of AISI H13 (46-47 HRC) and conducted experimental tests and finite simulation to investigate chip formation in high-and ultra-high-speed milling. He found that the serration of chips became increasingly obvious as the cutting speed increased, the formation frequency of a sawtooth increased with decreasing growth, and most of the sawtooth separated at a cutting speed of 2000 m/min.…”
Section: Introductionmentioning
confidence: 99%
“…Obikawa et al (2008) reported that by spraying small amount of lubrication, called micro-litre lubrication, on cutting zone using specially designed nozzle increased the tool life as compared to ordinary MQL spraying in machining of Inconel 718. Cui et al (2016) reported that the degree of chip serration increased and tool-chip contact length decreased with increase in cutting speed in high and ultra-high speed milling of AISI H13 hardened steel. They reported that the main tool wear pattern was flank wear.…”
Section: Introductionmentioning
confidence: 99%
“…An idea conveyed is that there are two cutting speeds at which the tool temperature will be the same and one of these is a much higher speed than the other. It is widely accepted that this was the start of the high speed machining (HSM) concept [1,4,5]. However, the appropriate cutting tool material was not available in that time.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions are contradicting but also supporting early theory. The topics involving high speed, temperature and wear are frequently reviewed [1,4,5]. The high speed machining was researched for turning and milling by various authors in conditions of either coated, uncoated cutting tools or dry and wet machining and different materials as the difficult to machined; hardened materials; stainless steel; alloys; composite materials etc.…”
Section: Introductionmentioning
confidence: 99%